2022
DOI: 10.1039/d1py01530c
|View full text |Cite
|
Sign up to set email alerts
|

The difference between photo-iniferter and conventional RAFT polymerization: high livingness enables the straightforward synthesis of multiblock copolymers

Abstract: Photo-iniferter (PI)-RAFT polymerization, the direct activation of chain transfer agents via light, is a fascinating polymerization technique, as it overcomes some restriction of conventional RAFT polymerization. As such, we elucidated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 57 publications
0
51
0
1
Order By: Relevance
“…9 Photochemically driven RAFT techniques have drawn significant attention over the conventional thermal process due to its mild reaction conditions and the possibility of spatiotemporal control, enabling potential applications such as three-dimensional (3D) printed materials. 10 Further, a recent study has reported the differences between photochemical and the traditional thermal RAFT polymerization using block polymers, 11 indicating superior livingness for the photochemical approach. In 2022, Foster et al showed a similar conclusion, demonstrating the superior control of PET-RAFT compared to conventional RAFT using multiblock star polymers.…”
mentioning
confidence: 99%
“…9 Photochemically driven RAFT techniques have drawn significant attention over the conventional thermal process due to its mild reaction conditions and the possibility of spatiotemporal control, enabling potential applications such as three-dimensional (3D) printed materials. 10 Further, a recent study has reported the differences between photochemical and the traditional thermal RAFT polymerization using block polymers, 11 indicating superior livingness for the photochemical approach. In 2022, Foster et al showed a similar conclusion, demonstrating the superior control of PET-RAFT compared to conventional RAFT using multiblock star polymers.…”
mentioning
confidence: 99%
“…This was even accomplished under visible light irradiation (450 nm) despite Xan possessing no noteworthy absorption capacity in this spectral region (Figure S2). Consequently, Xan can be used in a similar way as a photoinitiator, however with two important differences: 1) it will still take part in chain transfer equilibria and thus will be introduced as an end group in the polymer population; 2) the reversible deactivation provided by the thiocarbonylthio radical leads to an increased livingness, [22] likely as a result of the persistent radical effect. [27] Hence Xan can be added to an excess of a different CTA, and while the main CTA (CTA-2 from here on) maintains a narrow molecular weight distribution by efficient and fast chain transfer processes, the xanthate will fuel the polymerization, restrict termination by reversible deactivation, and create polymers that can be reactivated under irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…[19] However, chain transfer coefficients with more activated monomers (MAM)s are usually low, resulting in broad molecular weight distributions. [22] To control MAMs, other classes of CTAs like dithioesters or trithiocarbonates are more suitable. [23] However, the latter suffer from a comparably poor radical yield in PI-RAFT settings, rendering reaction times long and conversions not always high.…”
Section: Introductionmentioning
confidence: 99%
“…28 However, chain transfer coefficients with more activated monomers (MAM)s are usually low, resulting in broad molecular weight distributions. 34 To control MAMs, other classes of CTAs like dithioesters or trithiocarbonates are more suitable. 35 However, they suffer from a comparably poor radical yield in PI-RAFT settings, rendering reaction times long and conversions not always high.…”
Section: Introductionmentioning
confidence: 99%
“…In our proposed method the xanthate is only used in relatively minor quantities, to not influence the overall dispersity in a significant manner, while still being able to boost radical production and enable fast and highly living polymerization reactions, producing polymers that are inherently photo-active and can be chain-extended without the necessity for additional catalysts, sensitizers or initiator molecules. In this scenario, the xanthate acts similar to a photo-initiator, however with two important differences: 1) it will still take part in chain transfer equilibria 39 and thus will be introduced as an end group in the polymer population; 2) the reversible deactivation provided by thiocarbonylthio radicals leads to an increased livingness, 34 likely as a result of the persistent radical effect. 40 Hence the xanthate can be added to an excess of a different CTA, and while the main CTA (CTA-2 from here on) maintains a narrow molecular weight distribution by efficient and fast chain transfer processes, the xanthate will fuel the polymerization, restrict termination by reversible deactivation, and create polymers that can be reactivated under irradiation.…”
Section: Introductionmentioning
confidence: 99%